2021
DOI: 10.1115/1.4052774
|View full text |Cite
|
Sign up to set email alerts
|

Wind Tunnel Tests of a Model Small-Scale Horizontal-Axis Wind Turbine Developed From Blade Element Momentum Theory

Abstract: The small-scale horizontal-axis wind turbines (SHAWTs) have emerged as the promising alternative energy resource for the off-grid electrical power generation. These turbines primarily operate at low Reynolds number, low wind speed, and low tip speed ratio conditions. Under such circumstances, the airfoil selection and blade design of a SHAWT becomes a challenging task. The present work puts forward the necessary steps starting from the aerofoil selection to the blade design and analysis by means of blade eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…From Figure 16, one can specify that for the present SLT rotors C p (M1) > C p (M2) > C p (M3). A systematic twist across the blade section is often required to enhance the performance of straight bladed rotor, such as for the BEMT rotors (Schubel and Crossley, 2012; Siram et al, 2022a). Furthermore, even if the rotor blade is not modelled as per BEMT, a combination of a linear and non-linear twist on the blade is found to be promising (Rahgozar et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From Figure 16, one can specify that for the present SLT rotors C p (M1) > C p (M2) > C p (M3). A systematic twist across the blade section is often required to enhance the performance of straight bladed rotor, such as for the BEMT rotors (Schubel and Crossley, 2012; Siram et al, 2022a). Furthermore, even if the rotor blade is not modelled as per BEMT, a combination of a linear and non-linear twist on the blade is found to be promising (Rahgozar et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…For the present study, the errors in the inflow velocity, HWA signal, RTS output and rpm response is found to be around 1%, 0.5%, 1.2% and 2%, respectively, and the overall uncertainty in the evaluated C p value is found to be about 3.4%. The detail procedure has also been addressed in the reference article (Siram et al, 2022a).…”
mentioning
confidence: 99%
“…The aerodynamic behavior of 12 airfoils (Siram et al 2022) was examined using XFOIL and QBlade tools, and E216 was determined to have the highest lift to drag (L/D) ratio at a low Re, followed by SG6043. Furthermore, considering the maximum L/D ratio, maximum lift coefficient (Cl max), and stall angle (αstall) obtained from XFOIL (Drela and Youngren 2001), E216 had an L/D)max of 68.5, a Cl max of 1.5706, and an αstall of 13.5° at an Re of 10 5 , whereas SG6043 profile had an L/D)max of 66.5, a Cl max of 1.6491, and a αstall of 14.5°.…”
Section: Airfoil Selectionmentioning
confidence: 99%